Remnant of the Colonial Era: Telegraph Stations in Inggrisan Banyuwangi - Ainul Yaqin; Rohmatul Hasanah; Yuliastri (CV. Sekawan Siji, 2026)
During colonialism, Banyuwangi played an important role in the development of telecommunications and trade between countries, especially countries affiliated with European colonies. One of the historical legacies of colonialism in Banyuwangi is the British complex building which plays an important role in the history of Banyuwangi. This research will discuss the function and role of the Britishan complex in the history of Banyuwangi telecommunications and discuss the building style of the Britishan complex. The research method used is a historical research method which contains heuristics, criticism, interpretation, historiography. The results and discussion of this research are that the UK complex has an important role and function in telecommunications between Banyuwangi and Australia. The buildings in the British complex have a mix of Indies Empire building styles and ancient Javanese architecture.